Effects of Supplemental Vitamin D on Bone Health Outcomes in Women and Men in the VITamin D and OmegA‐3 TriaL (VITAL). (30th January 2020) - LeBoff, Meryl S; Chou, Sharon H; Murata, Elle M; Donlon, Catherine M; Cook, Nancy R; Mora, Samia; Lee, I‐Min; Kotler, Gregory; Bubes, Vadim; Buring, Julie E; Manson, JoAnn E
ABSTRACT: Although supplemental vitamin D is used to promote bone health in the general population, data from randomized controlled trials (RCTs) have been inconsistent. We determined whether daily, vitamin D3 supplementation improves bone mineral density (BMD) and/or structure. VITamin D and OmegA‐3 TriaL (VITAL) is a double‐blind, placebo‐controlled RCT of supplemental vitamin D3 (2000 IU/d) and/or omega‐3 fatty acids (1 g/d) in 25, 871 adults nationwide. This ancillary study included a subcohort of 771 participants (men ≥50 and women ≥55 years; not taking bone active medications) evaluated at baseline and at 2‐year follow‐up (89% retention). Total 25(OH)D levels were measured by liquid chromatography tandem mass spectrometry (Quest Diagnostics, San Juan Capistrano, CA, USA). Free 25(OH)D (FVD) levels were measured using the ELISA assay by Future Diagnostics Solutions BV (Wijchen, Netherlands). Primary endpoints were 2‐year changes in areal (a) BMD at the spine, hip, and whole body determined by dual‐energy X‐ray absorptiometry (DXA). Secondary endpoints were 2‐year changes in volumetric (v) BMD and cortical thickness at the radius and tibia assessed by peripheral quantitative computed tomography. Supplemental vitamin D3 versus placebo had no effect on 2‐year changes in aBMD at the spine (0.33% versus 0.17%; p = 0.55), femoral neck (−0.27% versus −0.68%; p = 0.16), total hip (−0.76% versus −0.95%; p = 0.23), or whole body (−0.22% versus −0.15%; p = 0.60), or on measures of bone structure. Effects did not vary by sex, race/ethnicity, body mass index, or 25(OH)D levels. Among participants with baseline FVD levels below the median (<14.2 pmol/L), there was a slight increase in spine aBMD (0.75% versus 0%; p = 0.043) and attenuation in loss of total hip aBMD (−0.42% versus −0.98%; p = 0.044) with vitamin D3 . Whether baseline FVD levels help to identify those more likely to benefit from supplementation warrants further study. Supplemental vitamin D3 versus placebo for 2 years in general healthy adults not selected for vitamin D insufficiency did not improve BMD or structure. © 2020 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research.